Risiko Pembiayaan dan Determinannya pada Perbankan Syariah di Indonesia - Rahmat Budiman; Noer Azam Achsani; Rifki Ismal (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2018)
One major problem of Islamic banking in Indonesia today is the high Non-Performing Financing (NPF) with its ratio amounted to 5.68% in June 2016. This paper aimed to identify and examine both macroeconomic and bank-specific factors affecting NPF ratio of Islamic banking. Particularly, it used the panel data regression method with a monthly data basis of eleven Islamic commercial banks in Indonesia. Furthermore, there were two periods examined i.e. from December 2011 to June 2016 (no specific restrictions on economic performance) and from February 2013 to January 2015 (restriction on economic performance). Technically, the dependent variable was NPF ratio (NPF) and the independent variables were Industrial Production Index (IPI), Real Sales Index (IPR), the difference between the BI Rate and inflation (BIREAL), the exchange rate of Rupiah against the US Dollar (EXR), the annual growth of financing (GFINY ), the ratio of financing to total assets (FINTA), the Capital Adequacy Ratio (CAR), Return on Assets ratio (ROA), the coverage of loan loss provision (CKPN), and the concentration of financing in the real estate sector (REFIN). The results showed that in the two periods examined, NPF was significantly influenced by the internal factors. In the first period, NPF was significantly influenced by GFINY, CKPN, and REFIN while in the second period, NPF was significantly influenced by CAR, ROA, CPKN, and REFIN. This shows that the quality of risk management implementation, profitability and capital are important factors in reducing the NPF ratio.Keywords: financing risk, credit risk, Islamic banking, panel data, fixed effects model